Ceramic Oxide MgO-SiO2-Al2O3 as Capacitor - Maryati Doloksaribu; Pintor Simamora; Mukti Hamjah Harahap; Kristin Kristin; Puspita Sari (Postgraduate, University of Mataram, 2023)
This study aims to analyze the effect of the composition MgO-SiO2-AL2O3 on dielectric constant, hardness, and microstructure. Good ceramics can be produced from an alloy of ceramic materials with a certain composition that is hard and able to store electric charge. Magnesium Oxide (MgO) ranked as the most heat-resistant insulating material for application practice. Silica (SiO2) is known for its hardness, besides that silica can also reduce plasticity and reduce dry shrinkage. The addition of alumina (AL2O3) to the ceramic resulted in a reduction in the mass of the ceramic. However, the hardness value obtained is increasing. So that the alloy between MgO-SiO2-AL2O3 is expected to produce ceramics that have superior mechanical and electrical properties. This study varied the composition of MgO-SiO2-AL2O3 with a composition ratio of 50%:50%:0%, 80%:15%:5%, 60%:32%:8%, 30%:63%,12%, 10%:75%:15%. Sintering was carried out at 12000C with a holding time of 8 hours. Then the sample's capacitance was measured using a capacitance meter and calculated the value of the dielectric constant, and hardness test using the Rockwell Hardness Tester type. The samples that have been tested for hardness are then taken three hardness values, namely low, medium, and high hardness to be tested for microstructure by SEM. The results show the MgO content increases, the value of the dielectric constant will increase but cause more pores. The level of SiO2-AL2O3 increases the higher the hardness value and the smaller the number of pores. Of the 5 samples that have been studied, the best sample used is sample 3 which has a good dielectric constant value, moderate hardness value, and the microstructure of the number of pores is not too much